2015
DOI: 10.3329/jdmc.v23i1.22695
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous needle tenotomy for Ponseti technique in the management of Congenital Talipes Equinovarus (CTEV)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Infection rate was found nil, whereas difficult procedure was observed in 5.71% of all cases. 22 In a study of Maranho DAC et al abnormal bleeding was found as the major complication (2 cases out of 57 cases) in cases of needle tenotomy, whereas in another study,15 difficult procedure was observed as the major problem (4 out of 70 cases). 12 In most of the study, complications are claimed as nil with needle tenotomy.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Infection rate was found nil, whereas difficult procedure was observed in 5.71% of all cases. 22 In a study of Maranho DAC et al abnormal bleeding was found as the major complication (2 cases out of 57 cases) in cases of needle tenotomy, whereas in another study,15 difficult procedure was observed as the major problem (4 out of 70 cases). 12 In most of the study, complications are claimed as nil with needle tenotomy.…”
Section: Discussionmentioning
confidence: 90%
“…18 Thereafter, similar studies were published by different authors describing this modified technique. [19][20][21][22] In literature review, different studies have been found regarding the complications of percutaneous needle tenotomy. [11][12][13][14][15] But in this study, no major complication has been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al also observed only minor bleeding complications in 11 out of 425 that were controlled with pressure over the wound [10]. Rahman et al also observed similar complications in nine out of 70 club feet [11]. Interestingly, the ankle dorsiflexion improved significantly after a one-year follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…The final 49 studies had a full-text review and only two were included in the final review. Six studies were identified through reference searches and included in the review, for a total of eight studies [12][13][14][15][16][17][18]21]. Seven studies were prospective cohort studies, and one study was an RCT.…”
Section: Systematic Review Findingsmentioning
confidence: 99%
“…Minokowitz et al were the first to describe Achilles tendon needle tenotomy in the literature with the use of a large bore needle as an alternative to a scalpel which is cost-effective, less disruptive for the family, and more comfortable for the child [11]. Although this technique has been reported in a number of literature, most of them have been conducted in Asian countries with no study or case series has been conducted in the United Kingdom [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%